Metodología de diseño y cálculo estructural para muros de contención con contrafuertes en el trasdos, basados en un programa de cómputo (2013)
In this degree work, a practical and didactic study of the subject known as Stabilization of slopes by means of retaining walls with buttresses has been carried out, and an attempt has been made to offer a basic understanding of design, with the intention of making known a little more this technique used in civil works, given its multiple economic and aesthetic advantages and its capacity to withstand efforts of any kind, being in several occasions the only feasible solution. Problems of soil stability. There are many factors that cause and characterize movements due to instability of a soil, these factors can be classified based on two main aspects; On the one hand, those directly related to the movable material such as topography, lithology, soil structure, etc., and on the other, external or indirect factors such as human action, environmental characteristics, humidity, earthquakes, etc. In this case, and depending on the properties of each soil, there will be risks of volumetric changes with changes in humidity, and / or a low support capacity. Specifically we will then have a floor that we must stabilize, to be able to use it avoiding the mentioned problems. To clarify concepts about the problem we are dealing with, we must analyze the following: -The stabilization of a floor is to minimize or prevent the freedom of movement of this, which is undesirable for the use we want to give. -There are different ways to stabilize a floor, currently the safest way to treat a floor is with the containment offered by a structure, in this case a retaining wall with buttress.